2012
DOI: 10.4028/www.scientific.net/amm.214.219
|View full text |Cite
|
Sign up to set email alerts
|

Applied Mechanics-Based Devices in Mobile Human-Computer Interaction

Abstract: To provide some suggestions of hardware specifications to relevant people, such as developers and researchers, this paper proposes a “standard” smart phone by using the revised value of parameters, like mean and mode, which are based on the analysis of smart phone hardware parameter information database. It provides a good reference for the human-computer interaction designers at both the qualitative and quantitative level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Corrosion attacks steel buildings mainly when the connections wait for welding on site. In the companion paper, a series of weld tests have been made [1]. The result shows that the surface rust can increase the level of porosity, reducing the weld strength by 5% on average.…”
Section: Effects Of Corrosionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrosion attacks steel buildings mainly when the connections wait for welding on site. In the companion paper, a series of weld tests have been made [1]. The result shows that the surface rust can increase the level of porosity, reducing the weld strength by 5% on average.…”
Section: Effects Of Corrosionmentioning
confidence: 99%
“…The companion paper [1] reported that rust may increase weld porosity, reducing the strength by 5% on average. In light of the variations in material strength, the effect of corrosion can be considered small.…”
Section: Effects Of Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reports the results of a series of tests on steel welds with and without rust on the welding surfaces. The companion paper further considers the effects of corrosion together with those of workmanship [1,2], assessing the seismic risk for existing buildings with steel moment frames. All that helps depict a complete picture of life-cycle performance evaluation of steel buildings subjected to corrosion and earthquake attacks.…”
Section: Introductionmentioning
confidence: 99%